Diagnosis and medical care for congenital cytomegalovirus infection: An observational study using claims data in Japan, 2010 to 2017. Issue 10 (March 2020) - Lin, Chiahsuan; Tomio, Jun; Tanaka, Hirokazu; Sonoda, Masaki; Sano, Kazuaki; Kobayashi, Yasuki
Abstract : Abstract: Although early detection and intervention may improve the outcome of the congenital cytomegalovirus (cCMV) infection, few studies assessed the real-world clinical practice for cCMV patients. We analyzed medical claims data to assess the patterns of diagnoses and medical care for cCMV patients. We used a subset of medical claims database (JMDC Claims Database) in Japan, covering 207, 547 newborns between April 2010 and March 2017 and observed for at least 6 months. The diagnosis of cCMV and related symptoms and sequelae and medical care, including essential examinations and antiviral treatment, were identified using standardized codes. Overall, we identified 53 (25.5 per 100, 000 newborns) cCMV patients diagnosed within 6 months after birth; of these, 83% were diagnosed within 1 month and 68% had at least 1 cCMV-related symptom at birth. Objective hearing tests and fundus examinations were performed within 6 months in 60% and 30% of patients, respectively. Antivirals were prescribed in 26% of patients. During the observation period (median = 33 months), sensorineural hearing loss (49%) and developmental problems (28%) were commonly identified as cCMV-related sequelae. The proportions of the patients continuously followed up with objective hearing tests up to 36 months were 30% in total and 56% in antiviral-treated patients, respectively. The cCMV patients did not necessarily receive a timely diagnosis nor continuous follow-ups in usual clinical practice. Although the universal screening for cCMV may, if implemented, facilitate early diagnosis, it should be accompanied by strategic follow-up plans to support timely interventions. Abstract : Supplemental Digital Content is available in the text